Fuzzy logic based fan controller of indoor air purifier fan - Ertie Cusipag Abana; Mark Jerson Palatan; Christian Paolo Pascual; Chia Mae Mateos; Sheree Anne Galasinao (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Indoor air purifier (IAP) has been developed by various companies worldwide to address indoor air pollution. The manufacturers of these air purifiers rarely concentrate in controlling the rotation speed of the fan which results in the use of traditional control techniques wherein some still relies on human intervention. In this paper, Fuzzy Logic (FL) was applied to control the rotation speed of the fan of an indoor air purifier. The system automatically maintains a suitable fan speed based on the fuzzy values generated on the current environmental condition. The series of testing conducted using the system showed a very high accuracy in the interpretation of dust concentration to its equivalent Air Quality Index (AQI) levels of health concern. For each detected AQI, the system was able to regulate the voltage coming into a motor that controls the speed of the fan. The usage of the fuzzy logic fan controller in the indoor air purifier fan reduced the energy consumption by 41.67%.